The Complexity of Cyber Security in Private and Professional Everyday Life — An Ethnographic-Informatic Collaborative Approach - Pöhls, Heinrich C.; Eckhardt, Dennis; Feist, Nelli; Pfeiffer, Sabine; Herrmann, Dominik; Katzenbeisser, Stefan (HCII: International Conference on Human-Computer Interaction, 2025)
In many ways it becomes visible that IT security problems persist in people’s everyday lives regardless of the progress in the field of IT security research. We show—based on ethnographic studies—that this is due to the complexity of everyday situations in which security mechanisms and device functionality and their heterogeneity interact with human understanding and everyday use in ways that are difficult to anticipate. To better align scientific research with people and their IT security needs, we have extracted five challenges that—if addressed—would lead to better IT security in people’s everyday lives. We contribute by the methodological development of interdisciplinary research showing how incorporating research methods from ethnography draws findings from the thoroughly subjective observation of the everyday life of individuals. IT security research can then make existing systems suitable for everyday use and develop new basic security functionalities tackling those five challenges that we found to be specific to everyday life: legacy systems, heterogeneity, versioning, perception, and everyday us
Keywords: Everyday Digitization; Ethnography; IT Security